PENGGUNAAN APE BISMU SEBAGAI REDESAIN ALAT PERMAINAN EDUKATIF UNTUK MENANAMKAN NILAI-NILAI KEMUHAMMADIYAHAN PADA GURU MI - Sumaryanti, Lilis; Laksana, Sigit Dwi; Setyaningrum, Krista Alifa; Rahayu, Vira Tri (Universitas Muhammadiyah Ponorogo, 2023)
Muhammadiyah education is very important and needs to be instilled in MI/SD children. In the educationalprocess, it is necessary to instill Muhammadiyah values to strengthen character values in children from anearly age. There are several partner problems including 1) still using simple APE to help teacher learningrelated to the introduction of Al-Islam Kemuhammadiyahan lessons; (2) there is no integration of generallearning with al Islam Kemuhammadiyahan; (3) there is no APE in the form of innovative APE related tothe introduction of Muhammadiyah values in children. The method used in this PKM is internalization inlearning activities, exemplary, and habituation with the empowerment model which includes: a) assessmentrelated to the mechanism of implementation of Focus Group Discussion (FGD); b) conducting workshopsto increase knowledge and skills in preparing RPP using Bismu's APE; c) technical guidance I to assist thepreparation of lesson plans using Bismu's APE; d) evaluation and reflection; The Educational Game Tool(APE) created is Bismu (Innovative Solutive Reading Beginning Bus). This Bismu is a redesign of the toybus vehicle that is often played by children in their daily lives. APE Bismu is designed with various kindsof games in each part including learning to read beginning which contains the values ofkemumahammadiyahan to be instilled in children including Islamic values, sincerity, tajdid, cooperation,and caring. The results of the activity are (1) Assistance in making Bismu APE; (2) 90% achievement oftraining on making Bismu APE; (3) the achievement of Learning Device Design using APE. This programexplains that all achievement targets are met by 90%, the level of training satisfaction is 96%.